EVALUASI KINERJA PENYULUH PERTANIAN DI BALAI PENYULUHAN PERTANIAN (BPP) DISTRIK MASNI KABUPATEN MANOKWARI - Sa'diyah, Siti Halimatus; Eftian Herdianto; Agus Irianto Sumule (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2024)
Masni District is one of the transmigration settlement areas that produces paddy and dryland rice commodities with a production of 3,806 tons and secondary crops 530 tons in 2020 (BPS Manokwari 2020). The Masni District Agricultural Extension Center has eight agricultural extension workers who assist farmers in thirty-two villages in an effort to increase agricultural production and strive to create farmer independence. The limited number of extension workers and technical constraints in the form of the availability of transportation with a wide working range of around 1,406.10km2 (BPS Manokwari, 2020), are suspected of affecting the performance of extension workers in achieving their goals so that an evaluation of each stage of the extension implementation is needed. The purpose of this study was to determine the performance of agricultural extension workers at the Masni District Agricultural Extension Center (BPP), Manokwari Regency. The research method used in this study is a descriptive method with a qualitative and quantitative approach. The sampling method used in this study was carried out by census. The results of the study showed that the evaluation results of the extension worker's performance were stated as good with the District Level Work Performance Value at a score of 79.22. This is supported by three indicators as parameters, namely the extension preparation indicator with an average score of 5 with a very good category, the extension implementation indicator with an average score of 3.6 with a good category and the evaluation and reporting indicator with an average score of 3.5 with a good category